Misliti v simbolih, ustvarjati avantgardno - Pranjić, Kristina (Slavistična revija, 2018)
This article examines the characteristics of Russian Silver Age art and literature, in particular the specifics of symbolist and avant-garde poetics and aesthetics, with the aim of determining to what extent the latter - the transgressive avant-garde movements - really break with symbolist traditions, and to what extent the relationship may be one of continuity and intensification of literary-artistic and worldview characteristics related to the Romantic tradition, on which both modernist phenomena were established at the beginning of the twentieth century.
Keywords: avantgarda; ruščina; simbolizem